Pengembangan Bahan Ajar Cerita Rakyat Berbasis Kearifan Lokal Kaliamntan Barat Dalam Pembelajaran Tematik Siswa Kelas IV MIN 3 Pontianak Tenggara - Tesa Hartianti; Siti Halidjah; Asmayani Salimi; Hery Kresnadi; Rio Pranata (Journal on Education, 2023)
This study aims to produce teaching materials for folklore based on local wisdom of West Kalimantan in thematic learning for fourth graders of Madrasah Ibtidaiyah Negeri 3 Pontianak Tenggara. This type of research is development research using the ADDIE model with analysis, design, development, implementation, and evaluation steps. Quantitative data sources in this study were the results of material expert validation, the results of media expert validation, and the results of filling out the practicality questionnaire of teaching materials by students and teachers. Qualitative data were obtained from notes, suggestions and comments from validators, teachers and students. Research instruments in the form of interview guidelines, questionnaires and documentation. The feasibility level of teaching materials validated to media experts obtained an average of 4.4 in the "Very Valid" category with the eligibility level of teaching materials validated to material experts obtaining an average of 4.3 in the "Very Valid" category. From the data validation results by two validators, an average recapitulation result of 4.3 can be obtained with the category "Very Valid" so that the teaching material is feasible to be tested. The practicality level of small-scale trial teaching materials obtained an average of 4.2 in the "Practical" category and the practicality level of large-scale trial teaching materials obtained an average of 4.4 in the "Very Practical" category. The results of research on the practicality of teaching materials by teachers obtained an average of 4.3 in the "Very Practical" category.